2013
DOI: 10.5539/ies.v6n10p1
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency at Faculties of Economics in the Czech Public Higher Education Institutions: Two Different Approaches

Abstract: The paper evaluates research and teaching efficiency at faculties of economics in the public higher education institutions in the Czech Republic. Evaluation is provided in two periods between the years 2006-2010 and 2007-2011. For this evaluation the Data Envelopment Analysis and Index approach are used. Data Envelopment Analysis measures research efficiency according to weighted inputs (average wages of academic staff, number of academic staff, and average number of students) to weighted output (RIV points).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…In higher education, there is no consensus on which variables to include for outputs, inputs, input prices, quality, and environment, and even to model the production process and the cost structure. We concentrate in non-for profit universities and university systems as a whole and do not consider economies of scale and scope studies in universities, and on departments' or other administrative units to study efficiency within one university, as for example in Flégl and Vltavská (2013) or in Martín (2016). Graduates, publications, and patents are the most common outputs for teaching and research activities, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In higher education, there is no consensus on which variables to include for outputs, inputs, input prices, quality, and environment, and even to model the production process and the cost structure. We concentrate in non-for profit universities and university systems as a whole and do not consider economies of scale and scope studies in universities, and on departments' or other administrative units to study efficiency within one university, as for example in Flégl and Vltavská (2013) or in Martín (2016). Graduates, publications, and patents are the most common outputs for teaching and research activities, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that in some studies, the efficiency of universities in the fields of education and research has been studied separately (36,41,42,48,53,69,76,87,88,101,104,106,118,126…”
Section: Discussionmentioning
confidence: 98%
“…Integration of the Czech Republic's into European structures resulted in joining the Bologna Declaration (Stastna & Walterova, 2014). The integration of the Bologna Declaration into Czech education system results in changing the university education system (Flegl & Vltavska, 2013;Musil &Fischer, 2015;Nedomova, Doucek, & Maryška, 2015;Sigmund, 2015;Sperkova & Nedomova, 2015) and opening and making available the study programs of Czech universities to foreign students (Kohanova, 2012;Kuncova & Mulac, 2015;OECD, 2009). Foreign students can apply for study program in Czech or for foreign-language study programs that are usually in English, German, or Russian.…”
Section: Introductionmentioning
confidence: 99%